The Prevalence of Extended-Spectrum Beta-Lactamase (ESBL) -Producing Escherichia Coli and Ingestion Levels in Farms in Sukabumi City - Irvan Aditya Prabowo; Yudith Vega Paramitadevi; Ika Sartika (Riviera Publishing, 2025)
This study examined the prevalence of Escherichia coli bacteria producing Extended-Spectrum Beta-Lactamase (ESBL) and modeled the ingestion rate in closed-house farms in Sukabumi. The results of the Monte Carlo simulation showed a range of daily fecal exposure (EED) between 0.0016 and 0.2417 grams per day, reflecting variations in worker activity, contact type, and cleanliness of the farm environment. Factors such as ingestion rate, the weight of stool adhering to gloves, and the frequency of hand-to-mouth contact affect exposure to pathogenic microbes, with higher ingestion rates associated with increased risk. Exposure is influenced by the type of activity, duration of contact, and level of hygiene; activities such as feeding and cleaning cages have the potential to cause high contamination. Monte Carlo-based probabilistic models and bootstrapping effectively describe the distribution of exposure and account for the uncertainty in the data, providing a basis for health risk mitigation policies related to exposure to resistant E. coli. These findings are important for the development of antimicrobial resistance control policies in the livestock sector, particularly for improving biosecurity measures to reduce AMR exposure in livestock workers.